Karsinoma Payudara pada Laki-Laki Laporan Kasus dan Tinjauan Pustaka - Endang Soetristi Endang Soetristi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
Carcinoma of the male breast occurs so infrequently. Several articles reported that the relative frequency ranges between 0.46% —2% of all breast carcinoma. The histologic types of the male breast carcinoma were relatively the same as in the female, but in the male, lobular carcinoma and carcinoma with metaplasia were never found. The disease commonly occurs in elderly men, from the late fifth through the seventh decade, and in women it usually occurs before menopause. This situation suggests that estrogen has an important role in the pathogenesis of breast carcinoma. Two cases of male breast carcinoma were reported. One occurred in a man aged 28 years. The histologic type was papillary carcinoma with mucoid degeneration. The other occurred in an older man aged 70 years with infiltrating duct carcinoma. The latter case could support the important role of estrogen in causing carcinoma. But the other one, cannot support this. It must be thought that there are other factors, such as in genetic syndromes. Key Words: male breast carcinoma — estrogen — oncology — genetic syndromes — neoplasm